2005
DOI: 10.1051/0004-6361:20041488
|View full text |Cite
|
Sign up to set email alerts
|

Multi-density model of the ionised gas in NGC 253 using radio recombination lines

Abstract: Abstract.We have imaged the H92α (8.3 GHz), H75α (15 GHz), and H166α (1.4 GHz) Radio Recombination Lines (RRLs) from NGC 253 at resolutions of 4.5 pc (0.4 ) , 2.5 pc (0.2 ) and 53 pc (4.5 ) respectively. The H92α line arises from individual compact sources, most of which possess radio continuum counterparts. The line widths range from ∼200 km s −1 for the sources near the radio nucleus to 70-100 km s −1 for the extranuclear ones. These lines are emitted by gas at a density ∼10 4 cm −3 . The remainder of the cm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 36 publications
(80 reference statements)
6
39
0
Order By: Relevance
“…The eastern source is detected at >10σ in continuum emission as well, but the peak is only detected at the ∼8σ level in H40α emission. Although all three sources had previous been detected in radio continuum emission (Mohan et al 2005;Kepley et al 2011), only (Anantharamaiah & Goss 1996) had previously shown radio recombination line emission from all three sources. The same structure is also seen in the Brγ image from Engelbracht et al (1998), but the source is only marginally resolved and does not appear to show the same peak in recombination line emission.…”
Section: Datamentioning
confidence: 96%
See 1 more Smart Citation
“…The eastern source is detected at >10σ in continuum emission as well, but the peak is only detected at the ∼8σ level in H40α emission. Although all three sources had previous been detected in radio continuum emission (Mohan et al 2005;Kepley et al 2011), only (Anantharamaiah & Goss 1996) had previously shown radio recombination line emission from all three sources. The same structure is also seen in the Brγ image from Engelbracht et al (1998), but the source is only marginally resolved and does not appear to show the same peak in recombination line emission.…”
Section: Datamentioning
confidence: 96%
“…Seaquist & Bell 1977;Mebold et al 1980;Anantharamaiah & Goss 1996;Puxley et al 1997;Mohan et al 2002Mohan et al , 2005Rodríguez-Rico et al 2006;Kepley et al 2011). This includes the detection of H40α emission by Puxley et al (1997).…”
Section: Introductionmentioning
confidence: 99%
“…The departure coefficients vary with electron density, and we use coefficients corresponding to densities of n e = 10 4 and 10 5 cm −3 to determine a range of T e values. Our choice of electron densities is primarily based on prior measurements of n e for H II regions in NGC 253, which find n e 10 4 cm −3 (Ulvestad & Antonucci 1997; Mohan et al 2005). In particular, Mohan et al (2005) found that only 10% of the H40α emission can be modeled with an n e = 10 4 cm −3 component and suggested that the presence of higher-density ionized gas is required to fit this emission.…”
Section: The Electron Temperaturementioning
confidence: 99%
“…Our choice of electron densities is primarily based on prior measurements of n e for H II regions in NGC 253, which find n e 10 4 cm −3 (Ulvestad & Antonucci 1997; Mohan et al 2005). In particular, Mohan et al (2005) found that only 10% of the H40α emission can be modeled with an n e = 10 4 cm −3 component and suggested that the presence of higher-density ionized gas is required to fit this emission. This is also consistent with modeling of the radio and millimeter continuum emission toward the Sgr B2 protocluster, which is composed of numerous (ultra)compact HII regions with n e ranging from 10 4 to 10 6 cm −3 (Schmiedeke et al 2016;Sánchez-Monge et al 2017).…”
Section: The Electron Temperaturementioning
confidence: 99%
“…The projected distance in pc is shown on both axes. The observed brightness distribution at 1.4 GHz(Mohan et al (2005)) is shown by the gray scale contours. solution (29),(30),(45),(46), the Eqs.…”
mentioning
confidence: 99%